Former Yugoslav Republic of Macedonia : Report on the Observance of Standards and Codes (ROSC), Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This report assesses Macedonia's corporate governance policy framework, and enforcement and compliance practices. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Macedonia. The report identifies a number of key recommendations as follows. The disclosure framework should be overhauled, as part of the on-going revision of the Securities Law. Shareholders should be required to disclose all direct and indirect ownership. The law should increase authority of the Macedonian Securities and Exchange Commission (MSEC), and especially its powers to impose sanctions, while MSEC should develop a strategy to use its new authority to improve corporate governance and shareholder rights. The Macedonian Stock Exchange (MSE) should complete the process of drafting a corporate governance code, should revise its listing rules in line with the Code and the new Securities Law, and consider the development of a "corporate governance tier". The exchange should fully implement a system of electronic information dissemination.